C# 12 in a nutshell : the definitive reference - Albahari, Joseph (Sebastopol, CA : O'Reilly Media, 2023)
"When you have questions about C# 12 or .NET 8, this best-selling guide has the answers you need. C# is a language of unusual flexibility and breadth, and with its continual growth, there's always so much more to learn. In the tradition of O'Reilly's Nutshell guides, this thoroughly updated edition is simply the best one-volume reference to the C# language available today."--Page [4] of cover.
Introducing C# and .NET -- C# language basics -- Creating types in C# -- Advanced C# -- .NET overview -- .NET fundamentals -- Collections -- LINQ queries -- LINQ operators -- LINQ to XML -- Other XML and JSON technologies -- Disposal and garbage collection -- Diagnostics -- Concurrency and asynchrony -- Streams and I/O -- Networking -- Assemblies -- Reflection and metadata -- Dynamic programming -- Cryptography -- Advanced threading -- Parallel programming -- Span<T> and Memory<T> -- Native and COM interoperability -- Regular expressions.
Includes index.
Keywords: C# (Computer program language); Programming languages (Electronic computers); C# (Langage de programmation); handbooks; Handbooks and manuals; Guides et manuels